Evaluation of the type housing and inclusion of flaxseed supplement “linum usitatisium l.” for the production egg enrichment with omega-3 fatty acids - Jaramillo Benavides, Alvaro Hugo (Revista Colombiana de Investigaciones Agroindustriales, 2018)
The following investigation had like objective evaluate the main productive parameters and of quality of the hen egg. The fatty acid profile of the yolk was quantified by gas chromatography and whole egg protein. Semi-healed laying hens were used comparing two housing systems: conventional floor, compared, compared a semi-free range system confined grazing system, and balanced diets were provided with the inclusion of 10% flax seed, during an experimental period of nine weeks. Conditions of improvement in animal welfare were used in the housing in pasture. An ANAVA was applied in a completely randomized design and for the sensory analysis the Chi-square test was applied. No statistical differences were found (p<0.05) in egg production, egg weight, conversion and egg mass during the experimental period in the two housings. Statistical differences were found (p<0.05) in the weight of the yolk. Regarding the fatty acid profile of the yolk, significant differences were found in most of these, mainly in the total of polyunsaturated fatty acids (PUFA), higher in the treatments with the inclusion of flaxseed. The α-linolenic (C18: 3) n-3 was statistically higher (P<0.05) with the inclusion of flaxseed in the two housings compared with the control. The concentrations of this fatty acid were 11.84 times higher with the inclusion of flaxseed compared to the control. A lower total omega 6/3 ratio was also found with the inclusion of flaxseed. Significant differences were found (p<0.05) with better flavor and color of the yolk in the lodging in pasture compared to the conventional floor. The economic assessment of the dietary treatments shows that it is feasible producing this type of egg enriched with omega 3 and in the evaluated lodging, as a functional food for the benefit of human health.